A Comparative Study of the Level of Depression among Students in the Hostel at Anbar University - Marwan Abdullatif (Journal of Global Pharma Technology, 2018)
Depression is one of the most common psychiatric diseases in the world, confirmed by global research. The World Health Organization (WHO) sees it as the second most important cause of death and disability in the world after heart disease by 2020. Depression is defined as "a temporary or permanent emotional state in which the individual feels constricted, sad, and distressed, and is characterized by feelings of concern and grief. This condition is accompanied by specific symptoms related to mood, cognitive, behavioral and physical aspects. This study is intended to highlight a very important subject for university students as it is a scientific attempt to study the level of depression they have, especially as this study focuses on an age group with hopes for the renaissance of the society. The problem of depression may be greater than it may come to mind, which is likely to be treated as an attempt to vent the excitement and enjoyment of the most important. For these reasons, depression has been the subject of continuous follow-up and study, and has been written about in many different cultures and different languages. Therefore, the current study is a preliminary step to understand this phenomenon and propose appropriate preventive and curative solutions to mitigate their powers and the associated problems. The research community included the students of some of the (117) faculties of internal departments in Anbar University, represented by three different faculties: College of Engineering, College of Science and College of Physical Education and Sports Sciences. The sample of the study was affected by (60) students, and by percentage (51.28%). They were chosen randomly, with 20 students per college.After collecting the information, they were unloaded in special tables, and the most important conclusions were reached:There are statistically significant differences between the students of some colleges residing in the internal departments at Anbar University in the level of depression.Students of the College of Science resident in the internal departments at Anbar University more students are prone to depression.Students of the College of Physical Education and Sports Sciences resident in the internal departments at Anbar University less students at the level of depression.Keywords: Depression, Students and hostel.